2013
DOI: 10.1097/fjc.0b013e318276d444
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Pharmacodynamics, and Tolerability of ACT-077825, a New Direct Renin Inhibitor After Multiple-ascending Doses in Healthy Subjects

Abstract: This study was conducted to characterize the multiple-dose tolerability, pharmacokinetics, and pharmacodynamics of ACT-077825, a new direct renin inhibitor, in healthy male subjects. In this single-center, double-blind, placebo-controlled, active-controlled (20 mg of enalapril), randomized multiple-ascending dose study, ACT-077825 was administered once a day. for 7 days in the 50-1000 mg dose range to sodium- and potassium-restricted subjects. ACT-077825 pharmacokinetics on days 1 and 7 were characterized by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The pharmacokinetic parameters determined in these healthy populations were in agreement with the previous pharmacokinetic investigations performed in healthy male subjects following escalating single oral doses (from 1 to 1,000 mg) of ACT-0775825 [6] as well as after repetitive administration of escalating doses during 7 days [9], confirming that the exposure (C max and AUC) of ACT-077825 was dose proportional for single doses ranging from 100 to 1,000 mg [6]. Furthermore, as previously reported [6], a double peak for C max was observed in all groups independently of age and sex, suggesting the presence of enterohepatic recycling of ACT-077825.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The pharmacokinetic parameters determined in these healthy populations were in agreement with the previous pharmacokinetic investigations performed in healthy male subjects following escalating single oral doses (from 1 to 1,000 mg) of ACT-0775825 [6] as well as after repetitive administration of escalating doses during 7 days [9], confirming that the exposure (C max and AUC) of ACT-077825 was dose proportional for single doses ranging from 100 to 1,000 mg [6]. Furthermore, as previously reported [6], a double peak for C max was observed in all groups independently of age and sex, suggesting the presence of enterohepatic recycling of ACT-077825.…”
Section: Discussionsupporting
confidence: 85%
“…The metabolic clearance of propranolol, a β-blocker substrate of CYP2D6, was significantly lower in females, leading to a 70% higher exposure [18]. It has been shown that ACT-077825 is a substrate of CYP3A4 [9,19] and it was reported that the clearance of many CYP3A substrates may be reduced with age, but no sex-related differences in clearance have been reported for these drugs [20]. However, the exposure to nefazodone, a substrate and inhibitor of CYP3A4, is 50% higher in elderly women compared to young subjects or elderly men [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, a new DRI, ACT-077825, was shown to have an adequate safety profile in humans when administered once daily. 103 ACT-077825 inhibits plasma renin activity, while the levels of immunoreactive renin increase, a pattern typical of DRIs. 102 However, the decrease in plasma renin activity is transient and is not dose-dependent at 7 days.…”
Section: Direct Renin Inhibitorsmentioning
confidence: 99%